ANALISIS KEUNGGULAN KOMPARATIF DAN KOMPETITIF PENGUSAHAAN KOMODITI JAGUNG DI KABUPATEN GROBOGAN (Studi Kasus: Desa Panunggalan, Kecamatan Pulokulon, Kabupaten Grobogan, Jawa Tengah) - Faroby Falatehan; Arif Wibowo (Departemen Agribisnis, FEM-IPB, 2008)
Corn is one of strategic commodities in Indonesia. Corn productivity from year to year continues to increase, but it is lower than the world productivity. This research analyzes the comparative and competitive advantages of corn farm management in Grobogan district, Central Java province. Corn is financially and economically profitable, besides that, it also has comparative and competitive advantages. Government policy on corn commodity has not been running effectively. The most sensitive component of the profit earned in corn commodity in Grobogan is a component of the output price.